Institutions and Institutional Change in the Management of Domestic Wastewater in Costa Rica (1886–2022): An Analysis from the Perspective of Douglass North - Mora González, Ana Lucía (2024)
This study examines the influence of institutional changes on the management of domestic wastewater in Costa Rica since the late 19th century. Its objective is to understand how transformations in both formal and informal institutions have affected the handling of these effluents in the country. It is based on Douglass North’s theoretical framework regarding institutions and institutional change, given its relevance in this field. The analysis focuses on the policies and practices adopted in response to sanitary and environmental challenges, relying on a documentary review that includes primary sources such as historical records. These policies have been the foundation of a system that has expanded from the capital to other regions at different rates. By 2024, over 70% of the country’s population still lack connection to sanitary sewer systems, highlighting the magnitude of the issue. The review is complemented by academic texts that expand on North’s theory, showing that both formal and informal rules have profoundly influenced the transformation of sanitation policies. Despite advancements, the discussion emphasizes that effective implementation remains a significant challenge. In conclusion, institutional changes have been fundamental to improve wastewater management in Costa Rica, although significant challenges persist to achieve more efficient management, such as improving the coverage of the provision of wastewater treatment plants that guarantee a return of water to the ecosystem in a safe way